A Study on Characteristics of High PM2.5 Pollution Observed around Large-scale Stationary Sources in Chungcheongnam-do Province - Son, Se Chang; Park, Seungshik; Bae, Minah; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2020)
In this study, pollution episodes of PM2.5 observed between May 07 and June 07, 2019 at air monitoring stationslocated around large-scale stationary sources in Chungcheongnam-do province were examined. Furthermore, local and regional contributions of PM2.5 measured during the pollution episodes were evaluated using Community Multiscale Air Quality (CMAQ) model. During the study period, two and three episodes were identified at stations around coal-fired power plants and a petrochemical complex (episodes I and II), and at stations around a steelworks and its downwind locations (episodes I, II, and III), respectively. Episode I occurred between May 15 and 17 was dominated by local pollution with very stable air conditions, and similar to the episode I, episode III (June 02~06) was also associated with stagnant weather pattern over the Korean Peninsula with some inflow of air pollutants from outside. On the contrary, episode II occurred between May 23 and 25 at all stations was strongly associated with long-range transportation of air pollutants from northern regions of China (e.g., Shanghai area). Average local and regional contributions of PM2.5 over 9 stations estimated using CMAQ model were 60.6 and 39.4%, 25.7 and 74.3%, and 41.3 and 58.7% during episodes I, II, and III, respectively. However, respective local contribution of PM2.5 observed at the station around a steelworks increased to 67.6, 40.0, and 56.2%, suggesting setting up effective reduction strategies of air pollutants such as SO2, NOx, and primary PM2.5 from the steelworks.
Keywords: Chungcheongnam-do; CMAQ model; Large-scale stationary sources; Local and regional contributions; PM2.5; Pollution episodes